2007
DOI: 10.1038/sj.onc.1210914
|View full text |Cite
|
Sign up to set email alerts
|

TMPRSS4 promotes invasion, migration and metastasis of human tumor cells by facilitating an epithelial–mesenchymal transition

Abstract: TMPRSS4 is a novel type II transmembrane serine protease found at the cell surface that is highly expressed in pancreatic, colon and gastric cancer tissues. However, the biological functions of TMPRSS4 in cancer are unknown. Here we show, using reverse transcription-PCR, that TMPRSS4 is highly elevated in lung cancer tissues compared with normal tissues and is also broadly expressed in a variety of human cancer cell lines. Knockdown of TMPRSS4 by small interfering RNA treatment in lung and colon cancer cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
140
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(146 citation statements)
references
References 41 publications
(44 reference statements)
6
140
0
Order By: Relevance
“…35 Since siRNA-TMPRSS4 has been proved to inhibit radiationinduced expression of TMPRSS4 and SIP1, thereby enhance E-cadherin expression and suppress radiationenhanced dissemination and metastasis in our study, we speculate that radiation-induced EMT may be mediated by TMPRSS4-induced SIP1. Though it is well established that TMPRSS4 can activate SIP1 and stimulate EMT via MAPK signaling pathway, 21,36 it is the first time by our study to demonstrate that TMPRSS4 is involved in radiation-induced EMT. However, since we could not rule out the possibility of other E-cadherin regulators such as Snail, Slug and Twist that may be involved in radiation-induced EMT, further study is essential to elucidate the mechanism involved in radiation-induced EMT.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…35 Since siRNA-TMPRSS4 has been proved to inhibit radiationinduced expression of TMPRSS4 and SIP1, thereby enhance E-cadherin expression and suppress radiationenhanced dissemination and metastasis in our study, we speculate that radiation-induced EMT may be mediated by TMPRSS4-induced SIP1. Though it is well established that TMPRSS4 can activate SIP1 and stimulate EMT via MAPK signaling pathway, 21,36 it is the first time by our study to demonstrate that TMPRSS4 is involved in radiation-induced EMT. However, since we could not rule out the possibility of other E-cadherin regulators such as Snail, Slug and Twist that may be involved in radiation-induced EMT, further study is essential to elucidate the mechanism involved in radiation-induced EMT.…”
Section: Discussionmentioning
confidence: 63%
“…TMPRSS4 is a novel type II transmembrane serine protease found at the cell surface and is highly expressed in a variety of cancer tissues. 21,34 SIP1 is one of the prominent EMT-inducing regulators that repress E-cadherin transcription via interaction with specific E-boxes of the proximal E-cadherin promoter. 35 Since siRNA-TMPRSS4 has been proved to inhibit radiationinduced expression of TMPRSS4 and SIP1, thereby enhance E-cadherin expression and suppress radiationenhanced dissemination and metastasis in our study, we speculate that radiation-induced EMT may be mediated by TMPRSS4-induced SIP1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that some prostanoids derived from COXs suppress ovarian tumor growth and that specific inhibition of EP receptor-mediated cell signaling is a valid therapeutic strategy for peritoneal metastasis of ovarian cancer. TMPRSS4 promotes tumor growth, invasion, metastasis, and epithelialmesenchymal transition (15,34). Considering the function of TMPRSS4 in cancer cells, our data showing inhibition of cancer cell growth in SKOV/ip-FuEP2/Ex2-based peritoneal metastasis model are reasonable, and the ineffectiveness of AEBSF alone or in combination with meloxicam may be a result of the expression level of TMPRSS4 being insufficient to suppress cancer cell growth.…”
Section: Discussionmentioning
confidence: 60%
“…Kebebew et al reported that TMPRSS4 mRNA expression was higher in malignant than in benign thyroid neoplasms and could improve the diagnostic accuracy of fine needle aspiration biopsy [13]. Jung and colleagues showed that TMPRSS4 promoted invasion, migration and metastasis of human tumor cells by facilitating an epithelial-mesenchymal transition [14]. Subsequebt data show that TMPRSS4 induces invasion and epithelial-mesenchymal transition through upregulation of integrin alpha5 and its signaling pathways [15].…”
Section: Discussionmentioning
confidence: 99%